Annual Report and Accounts For the year ended 30th June, 1986 (The Southern African Institute of Mining and Metallurgy, 1986)
PREFACE During the past year, the Council of the SAIMM undertook a major strategic-planning exercise to review all its current activities, and to redefine its scope and objectives in the light of changing circumstances. The following are the four main concerns that prompted Council to take stock of the situation. (1) Over the past five years, the SAIMM has become heavily involved in a variety of new activities. (There are many examples, of which the expansion in book publications and the establishment of physical metallurgy as a third major discipline with its own colloquia and schools are perhaps the most important.) While these new activities have considerably broadened the SAIMM's scope, they have resulted in a significant increase in the day-to-day workload of the President, Office Bearers, and Council members, and of the secretarial staff based at Kelvin House.